Modeling and simulation of WSNs for agriculture applications using dynamic transmit power control algorithm - Latifah Munirah, Kamarudin; R. Badlishah, Ahmad, Prof. Dr.; Ndzi, David, Dr.; Ammar, Zakaria; Ong, Bi Lynn, Dr.; Kamarulzaman, Kamarudin; Azizi, Harun; S. M., Mamduh (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/